A review of modeling and simulation tools for microgrids based on solar photovoltaics - Seane, T. B.; Samikannu, R.; Bader, T. (Frontiers in Energy Research, 2022)
Solar Photo Voltaic (PV) powered community microgrids are a promising sustainable solution for neighborhoods, residential quarters, and cities in sub-Saharan Africa (SSA) to meet their energy demands locally and to increase energy independence and resilience. This review provides a comprehensive study on the nature of solar PV community microgrids. Through their capacity to operate in both grid-connected and island modes, community microgrids improve utility system resiliency while also boosting energy security in local states and towns. The integration of solar PV microgrids with the electricity utility grid requires control strategies to facilitate the load sharing between distributed generation units, voltage and frequency control, as well as emergency islanding. Control strategies such as hierarchical control and droop are discussed in the review article. To identify the effectiveness of control strategies through system simulation, a review of various modeling designs of individual components in a solar PV microgrid system is discussed. The article goes on to talk about energy optimization approaches and their economic impact on microgrid systems. Finally, the review concludes with an overview of the technical challenges encountered in the integration of solar PV systems in microgrids.